New model for making resilient decisions in an uncertain context: The rational resilience-based decision-making model (R2DM) - Said, Saloua; Bouloiz, Hafida; Gallab, Maryam (Decision Making: Applications in Management and Engineering, 2023)
The present paper came into existence with the specific purpose of providing an optimized process that enables making resilient decisions in an uncertain context, and here our interest is particularly focused on the activity of new venture creation and on the entrepreneurial decision-making logic, in particular, effectuation theory. Within this framework, the rational resilience-based decision-making model (R2DM) is introduced. The relevant steps of this model are: (1) The identification of the problem and the available options. In this instance, the studied situation is the effectual customer co-creation case, and the available alternatives are planning, visionary, adaptative and transforming approaches, (2) The definition of the selection criteria that should be used to evaluate the available alternatives. In our case, these criteria are the six principles of entrepreneurial resilience, which are set out in detail, (3) The choice of the methodology to be followed in assessing the available options. To that end, three interconnected methods, based mainly on logical thinking and reasoning, are proposed. They are respectively devoted to Entrepreneurial resilience (ER) calculation, options classification using logistic regression algorithm, and the determination of the most resilient route to reach objectives employing graph theory. The obtained results are compared to what is advocated in the literature and conclusions are made.